New activities, the welfare cost of uncertainty and investment policies - Aizenman, Joshua 1949- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 1996)
This paper studies the effect of policy uncertainty on the formation of new activities in Romer's (1994) type of an economy, where productivity of labor increases with the number of capital goods. Adding a new capital good requires a capital specific set-up cost, invested prior to using the capital good. Agents are disappointment averse, putting greater utility weight on downside risk [as modeled by Gul (1991)]. Policy uncertainty is induced by the Disappointment aversion implies that investment, labor and capitalists' income drop at a rate proportional to the standard deviation of the tax rate. Hence, policy uncertainty induces first-order adverse effects, whereas policy uncertainty leads to second-order effects when consumers maximize the conventional expected utility. The adverse effects of policy uncertainty can be partially overcome by a proper investment policy. The paper interprets the tax concessions granted to multinationals as a commitment device that helps overcoming the adverse implications of policy uncertainty.